On Identification of the System with Space-Distributed Parameters - Masłowski, A. (Engineering Transactions, 1975)
We consider the problem of the state identification of the deterministic systems with space-distributed parameters, described by differential or integral equations. Formulation of the problem was based on the model of dynamics and observations of the systems in question as well as on the proposed error functional. Conditions for the optimal solution were discussed with the use of dynamic programming and maximum principle.